2013
DOI: 10.1016/j.jorganchem.2013.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Bis(diphenylphosphino)acetylene as bifunctional ligand in cycloplatinated complexes: Synthesis, characterization, crystal structures and mechanism of MeI oxidative addition

Abstract: Binuclear cycloplatinated(II) complexes with general formula of [Pt 2 Me 2 (C^N) 2 (m-dppac)], (1, ĈN ¼ deprotonated 2-phenylpyridine (ppy); 2, ĈN ¼ deprotonated benzo{h}quinoline (bhq)) in which dppac ¼ 1,1 0-bis(diphenylphosphino)acetylene, are synthesized by the reaction of [PtMe(SMe 2)(C^N)] with 0.5 equiv of dppac at room temperature. The complexes are fully characterized using multinuclear (1 H, 31 P and 195 Pt) NMR spectroscopy and complex 2 is further identified by single crystal X-ray structure determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…1-3 2-Phenylpyridine is a typical compound, and its reaction with a transition metal complex forms an orthometalated intermediate with the help of nitrogen coordination to the metal. [8][9][10] Electron density on the Pt (II) center of a [PtR 2 (LL)] complex can be manipulated by selecting R ligand, which has either electron-withdrawing or electron-donating ability. 4 In this type of cyclometalation, the two nitrogen atoms of bpy at first coordinate to metal and then the coordination of one nitrogen to the metal is switched to carbon-metal bond by rotation of the pyridine ring (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…1-3 2-Phenylpyridine is a typical compound, and its reaction with a transition metal complex forms an orthometalated intermediate with the help of nitrogen coordination to the metal. [8][9][10] Electron density on the Pt (II) center of a [PtR 2 (LL)] complex can be manipulated by selecting R ligand, which has either electron-withdrawing or electron-donating ability. 4 In this type of cyclometalation, the two nitrogen atoms of bpy at first coordinate to metal and then the coordination of one nitrogen to the metal is switched to carbon-metal bond by rotation of the pyridine ring (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…2 Although the most well-studied examples of these compounds are five-membered ring complexes containing N−Pt−C(phenyl) moiety, [3][4][5] six-membered cyclometalated complexes are relatively rare. [12][13][14][15][16][17][18][19][20][21] For example, the trans or cis oxidative additions of an alkyl halide to cyclometalated platinum(II) complexes give the corresponding alkyl-cyclometalated platinum(IV) complex. [12][13][14][15][16][17][18][19][20][21] For example, the trans or cis oxidative additions of an alkyl halide to cyclometalated platinum(II) complexes give the corresponding alkyl-cyclometalated platinum(IV) complex.…”
mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 In a two-step oxidative addition reaction of this type of complexes with no metal-metal bond, it is suggested that the first addition occurs faster than the second. [23][24][25]27 In the present study, we…”
Section: Single and Double Mei Oxidative Addition On Dimer Complexmentioning
confidence: 86%
“…The oxidative additions of alkyl halides to bridged binuclear platinum complexes have been briefly investigated and can yield products formed by single or double oxidative addition. [22][23][24][25][26][27] Also in recent years there has been a great interest in investigating the application of binuclear platinum(II) complexes in the field of platinum chemotherapy. 28 Therefore, it is interesting to extend the theoretical studies of monoplatinum complexes by studying binuclear complexes containing two platinum centers.…”
Section: Introductionmentioning
confidence: 99%